ANALYSIS OF KNOWLEDGE MANAGEMENT APPLICATION IN PT. BANK MANDIRI, Tbk - Usep Deden Suherman (Komitmen: Jurnal Ilmiah Manajemen, 2020)
Knowledge management as a process of accumulation of knowledge to improve organizational competitiveness is not only determined by the behavior of individuals and groups within the organization, strong desires and organizing also absolutely require organizational intervention to shape their desires and management. This study aims to determine and analyze the application of Knowledge Management in PT. Bank Mandiri, Tbk. This research uses a qualitative research approach. Data collection techniques are done through online interviews with Bank Mandiri employees. The results of the study revealed that the Bank Mandiri in the application of knowledge management (KM) is done by integrating into the corporate culture. Bank Mandiri awards MEA to employees who have a high learning culture, so many employees are competing to learn to obtain the MEA degree, with the high level of learning the employees will increase productivity, progress for the company and have the potential to create new knowledge. In addition, Bank Mandiri has also established a learning center for training for its employees. The company provides training to its employees in accordance with the work of each employee, then at the same place employees can share their knowledge with other employees, so that knowledge distribution is spread across all units. The culture of knowledge sharing at Bank Mandiri has become a culture for each of its employees, so that knowledge can be spread quickly and directed, which in turn can lead companies to become companies that can compete in the era of globalization.